Métodos de apropiación de la inteligencia artificial en la enseñanza de idiomas y sus consideraciones éticas - Wexell Machado, Luis Eduardo (2024)
In this article we examine the integration of artificial intelligence (AI) into language teaching at the Instituto Superior de Lenguas (ISL) of the Universidad Nacional de Asunción (UNA), Paraguay. We explore both the benefits and ethical challenges that emerge with the use of AI in educational contexts. Methodologically, this research is exploratory and follows a qualitative approach. Our sample includes eighty-eight ISL teachers, and we used a questionnaire to collect information on how AI is applied in teaching, learning, and assessment processes. The findings indicate that AI enhances educational efficiency by providing immediate feedback, customizing content to student levels, and enabling interactive activities. However, our study also reveals ethical concerns among teachers, especially regarding excessive reliance on AI, the potential reduction in human interaction during teaching, and issues of fairness in assessment. We conclude by emphasizing the importance of balancing AI usage with human critical judgment to ensure that technological tools effectively complement the teacher’s role in instruction and evaluation.